2017
DOI: 10.1515/ijhp-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of interdisciplinary preoperative patient education in foot and ankle surgery: immediate effects on knowledge, satisfaction and anxiety / Entwicklung und erste Evaluation eines präoperativen interdisziplinären Schulungskonzeptes für Patienten/-innen der Fußchirurgie: unmittelbare Effekte auf Wissenszuwachs, Zufriedenheit und Angst

Abstract: Background and objective: Foot and ankle surgery is increasing due to demographic and lifestyle changes. Most often, pa-tients are required to unload their foot postoperatively, resulting in significant impairment of activi-ties of daily living without adequate preparation for this situation. The aim of the study was the development and evaluation of a preoperative patient education intervention. Methods: Based on current research, a patient education intervention was developed. To investigate immediate effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This way, 15 studies were included in our review (Fig. 1) [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This way, 15 studies were included in our review (Fig. 1) [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%
“…All but one studies were published in English [25][26][27][28][29][30][31][33][34][35][36][37][38][39], and most of them assessed a broader population than only patients undergoing foot and ankle surgery [25-31, 33, 37-39]. Six of 15 studies were carried out in Europe [32,[34][35][36], five [26][27][28][29]31] in the USA, three [37][38][39] in Asia, and one [30] in Africa. Figure 2 shows the date of publication of studies separated by continent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 91 Another study from Germany evaluated the effect of a 2½-hour preoperative multidisciplinary training course that included education on the procedure, perioperative expectations, and postoperative protocols followed by an opportunity to practice ambulating with assistive devices. 80 Following intervention, they reported significant improvement in patient knowledge and satisfaction, but no effect on preoperative anxiety. 80 An additional 2 studies from the United Kingdom found that preoperative educational interventions led to significantly reduced length of hospital stay.…”
Section: Background: Prehabilitation In Orthopaedic Surgerymentioning
confidence: 96%
“… 80 Following intervention, they reported significant improvement in patient knowledge and satisfaction, but no effect on preoperative anxiety. 80 An additional 2 studies from the United Kingdom found that preoperative educational interventions led to significantly reduced length of hospital stay. 81 , 95 Selvan et al 81 set up a single course 3 weeks before surgery led by a nurse who provided education on the procedure and postoperative course and a physical therapist who reviewed postoperative weightbearing restriction, evaluated mobility, and instructed on stair navigation and safe use of crutches.…”
Section: Background: Prehabilitation In Orthopaedic Surgerymentioning
confidence: 96%